Contrasting roles of gibberellin and cytokinin in the in vitro development and acclimatization of pitaya (Selenicereus undatus (Haw.) D. R. Hunt) - Dias do Valle, Karminne; Lima Dias, Lana Laene; Damásio da Costa Júnior, Otalício; Zildo da Silva, Givanildo; Lemes da Silva, Maurecilne; Pereira da Silva, Danielle Fabiola; Diego Ismael (Revista Ceres, 2025)
The use of plant growth regulators is a widely adopted strategy to optimize germination and propagation under in vitro conditions; however, their application can also cause morpho-physiological changes in plants that need to be investigated. The study aimed to evaluate the effect of gibberellic acid (GA) and 6-benzyladenine (BA) supplementation on the in vitro germination, structure, and shoot proliferation of S. undatus, as well as to test different substrates during the acclimatization of the obtained plantlets. Seeds were inoculated in MS medium without plant growth regulators (MS0) and in MS medium supplemented with GA (1.0 and 3.0 mg L-1) and BA (1.0 and 2.0 mg L-1). Seeds were also germinated under ex vitro conditions as a control. In vitro culture conditions accelerated germination and initial development of S. undatus. However, GA supplementation did not influence seed germination speed. Greater hypocotyl and epicotyl lengths were obtained in plants grown in a medium supplemented with 1 mg L-1 GA. Regardless of the concentration, BA led to the emergence of multiple axillary shoots, altering seedling architecture. Furthermore, BA and GA acted antagonistically on the morphoanatomy of the hypocotyls, increasing and decreasing the thickness of this organ, respectively. The treatments supplemented with BA regenerated twice the number of plantlets per seed. The commercial substrate allowed a higher survival rate ( 85%) of the plantlets compared to sand ( 30%), and it has been recommended for acclimating S. undatus plantlets obtained through in vitro propagation.